Innovative teaching in higher education: Teachers' perceptions of support and constraint. Issue 2 (4th March 2021) - Gilbert, Amanda; Tait-McCutcheon, Sandi; Knewstubb, Bernadette
ABSTRACT: Rapid developments in ideas of knowledge, the role of educational technologies and the needs of students suggest that innovation is important in higher education. However, many factors can affect how and whether innovation occurs. In a study of identified innovative teachers, five thematic dimensions were identified that served to support or constrain pedagogical innovation: the teacher, the institution, colleagues, students and the teaching environment. In this paper we discuss the ways in which innovative teachers experienced each theme within their practice. We also consider how individuals and institutions might better support pedagogical innovation.